Incidence of Symptomatic COVID-19 in Unvaccinated Patients Within One Month After Elective Total Joint Arthroplasty: A Multicenter Study - Erfan Sheikhbahaei, MD; Seyed Peyman Mirghaderi; Alireza Moharrami, MD; Danial Habibi, PhD; Mehdi Motififard, MD; Seyed Mohammad Javad Mortazavi, MD (Arthroplasty Today, 2022)
Background: The safety of continuing total joint arthroplasty (TJA), as an elective procedure, during the pandemic is controversial. The present study aimed to investigate the incidence of symptomatic coronavirus disease 2019 (COVID-19) and its related risk factors in unvaccinated patients after TJA within 1 month after discharge in 2 large cities of our country. Material and methods: The present prospective study included all the patients admitted to 3 hospitals, located in Tehran and Isfahan, 2 highly populated cities of Iran, from April 1, 2020, to April 1, 2021, for elective TJA. Urgent TJA (traumatic fractures) were excluded. The primary outcome was symptomatic COVID-19 within 1 month after discharge that was diagnosed using the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) reverse transcription polymerase chain reaction test. Afterward, the incidence of COVID-19 in the study population was compared with that in the general population to estimate the safety of elective TJA during the pandemic. Results: From the 1007 patients undergoing TJA, 755 patients met the inclusion criteria. None of the patients was vaccinated against COVID-19. Among them, 18 patients (2.4%) developed symptomatic COVID-19 within 1 month after discharge. In the same time interval, the incidence of COVID-19 was 2.2% in the general population of these 2 cities, which was similar to the incidence reported in the study population. Of the patients who were positive for COVID-19, 4 patients were hospitalized, and 3 of them were admitted to an intensive care unit; however, no mortality was reported. Conclusion: The TJA will be a safe elective procedure for the patients during the pandemic if the preventive protocols are followed strictly.